Implementation of the Application for Organizing 3d Digital- Based Virtual Exhibitions in the Mice Industry of Medan City - Saragih, Agus Mariani; ., Jumjuma; Nasution, Lily Maryam; Anggraini, Juni (Journal of Ecohumanism, 2025)
The aim of this research is to develop a 3D Digital-based exhibition organizer industry so that it can have a global market by increasing the competitiveness of the exhibition event business market. This research was conducted with 50 event organizers as sample as well as population who are members of the Association of Indonesian Exhibition Companies (ASPERAPI). The implementation of this virtual exhibition application is carried out by providing tutorials and creating exhibition projects. The analysis using experimental method with descriptive statistical tests of rating results. The research results produced 6 virtual exhibition event projects designed by samples grouped into 6 groups. Then the results of the virtual exhibition event project are assessed by the instructor and rated. For quantitative testing, the results of questionnaires from participants (sample) were analyzed and resulted in the conclusion that the use of applications for organizing virtual exhibition events has advantages such as being easy to use, can be used for any type of exhibition and is small or large in scope. Meanwhile, the weakness is that participants and visitors in organizing this virtual exhibition event must have digital technology knowledge and skills.